An Electronic Examinations Framework with Electronic Free Handwriting - Deborah Natumanya; Evarist Nabaasa (CV. Literasi Indonesia, 2022)
Institutions of higher learning in developing countries are gradually embracing electronic examinations as a result of Covid-19 standard operating procedures that emphasize social distancing. However acquiring secure and acceptable electronic examinations has been a challenge as most of the available electronic examination systems are constrained by limited question types, highly reliant on keyboard typing, and lack of an electronic answer booklet. The electronic examinations framework with free handwriting presented in this paper seeks to address all the aforementioned challenges in-order to improve the usage and security of electronic examinations. To achieve the aforementioned goal, design science methodology was. Results obtained indicated that for usage and security to be eased, various parameters should be put in place i.e. user-friendly interfaces, authentication mechanisms, electronic examination setting, marking and attempt with electronic free-handwriting, electronic results, and a repository for student and lecturer data. The research output/artifact will be beneficial to Students, Lecturers and Institutional administrators.